MANAJEMEN TEKNOLOGI INFORMASI DAN KOMUNIKASI PASCA COVID DI DUNIA HARAPAN SCHOOL MAKASSAR - Nuraisah; Andi Ratu Ayuashari Anwar; By Tri Agung Nusantara Kr. J. Tompong (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the management of Information and Communication Technology (ICT) at Dunia Harapan School. The purposes of the study are to discover 1) the application of ICT based on 3 ICT components at Dunia Harapan School; 2) the ICT management at Dunia Harapan School; and 3) the supporting and inhibiting factors of ICT at Dunia Harapan School. This type of research is qualitative with a descriptive approach. The results of the study reveal that 1) the application of Information and Communication Technology at Dunia Harapan School based on 3 ICT components, namely the first hardware used, hardware that complies with ICT readiness standards in schools. Second, there are several applications used after the pandemic which are used to date in the new normal era, namely the Talenta application, Ed Connect, Google Classroom, and Zoom. Finally, the user, in this case the school operator, has one operator; 2) the management of Information and Communication Technology at Dunia Harapan, namely the first, planning is conducted based on the school's vision and mission and application selection strategies according to school needs. Furthermore, the organizers where the school does not have its own structure related to ICT/ management so that some of the applications used are handled by one operator, and finally supervision is conducted by the principal and evaluation is conducted at regular school meetings; 3) the supporting factors for the management of Information and Communication Technology at Dunia Harapan School are the hardware and software possessed are adequate and appropriate, and the level of understanding of utilizing ICT applications or devices by school members, while the inhibiting factor is an unstable network